DISKURSUS FEMINISME TRANSNASIONAL: PENGARUH INTERSEKSIONALITAS DALAM AGENDA KEAMANAN MANUSIA DI ASIA TENGGARA - Rini Afriantari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2019)
The emergence of feminism after global political depolarization after September 11, 2001, has a strategic role in designing the security agenda of a sovereign country with the emergence of the intersexional paradigm. In Southeast Asia, the excitement of the securitization of the non-traditional security agenda sprang up among regional authorities. Unfortunately, the security depolarization agenda is not followed by gender analysis where the state still uses realism among patriarchal global political hierarchies and excludes women in the global political arena. In this paper, the author will analyze how intersexionality in the agenda of human security in Southeast Asia emphasizes the discourse of transnational feminism.